2022
DOI: 10.1136/bmjopen-2021-058408
|View full text |Cite
|
Sign up to set email alerts
|

On the road to universal coverage of postnatal care: considerations for a targeted postnatal care approach for at-risk mother–baby dyads in low-income and middle-income countries informed by a consultation with global experts

Abstract: IntroductionThe potential of timely, quality postnatal care (PNC) to reduce maternal and newborn mortality and to advance progress toward universal health coverage (UHC) is well-documented. Yet, in many low-income and middle-income countries, coverage of PNC remains low. Risk-stratified approaches can maximise limited resources by targeting mother–baby dyads meeting the evidence-based risk criteria which predict poor postnatal outcomes.ObjectivesTo review evidence-based risk criteria for identification of at-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Other factors may be infeasible for identification by CHWs (e.g., body mass index, maternal nutritional status), or may result in stigma (e.g., income, employment status, tribe/caste). As Muriuki et al [109] note, risk factors will need to be selected with consideration of relevance in the context, and feasibility for identification. Importantly, although clinical factors were not identified as part of this scoping review, any risk screening for mother-baby dyads must also include known clinical risk factors (e.g., heavy bleeding in delivery).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors may be infeasible for identification by CHWs (e.g., body mass index, maternal nutritional status), or may result in stigma (e.g., income, employment status, tribe/caste). As Muriuki et al [109] note, risk factors will need to be selected with consideration of relevance in the context, and feasibility for identification. Importantly, although clinical factors were not identified as part of this scoping review, any risk screening for mother-baby dyads must also include known clinical risk factors (e.g., heavy bleeding in delivery).…”
Section: Discussionmentioning
confidence: 99%
“…Although the study identified several risk factors associated with increased neonatal mortality, it is important to note that all pregnancies and deliveries are inherently high-risk events; adverse outcomes may occur even in mother-baby dyads with no identifiable risk. A targeted PNC approach should be considered only in the context of broader efforts to improve coverage and quality of PNC, so that mother-baby dyads without identifiable risk factors receive timely PNC [109]. These findings also point to risk factors that should be mitigated; comprehensive, multisectoral "upstream" efforts to reduce the prevalence of risk factors will lead to improvements in maternal and newborn outcomes.…”
Section: Plos Onementioning
confidence: 99%
“…However, the effect of a one-year lag in postpartum visits on U5MR was significant and it could reduce U5MR. The potential of timely, quality postnatal visits in reducing U5MR is well documented [55,56]. In addition to neonatal diseases, the common causes of U5MR are important infections like lower respiratory infections, pneumonia [57], diarrhoea, and meningitis [58], which a relatively long duration and can be effectively prevented by means of scientific feeding and care.…”
Section: U5mr and Maternal Health Services Utilization Ratementioning
confidence: 99%
“…At the community level, FWAs are supported to provide targeted postnatal HVs, prioritizing mother-baby dyads who are identified to have risk factors, including clinical and nonclinical (e.g., aged <20 years and primiparity). 30 With the targeted PNC approach, FTMs, including those who deliver at home, are prioritized for FWA outreach. FWAs distribute a mother-baby booklet written for girls and young women becoming FTMs and their male partners, and a printed invitation card that invites FTMs to access RMNCH services, including PPFP, from the closest health facility.…”
Section: Final Approaches Selected Based On Potential For Impact and ...mentioning
confidence: 99%